Real‐time tracking of fibrinolysis under constant wall shear and various pulsatile flows in an in‐vitro thrombolysis model - Ziqian Zeng; Alexei Christodoulides; Nathan J. Alves (Wiley, 2023)
Abstract A great need exists for the development of a more representative in‐vitro model to efficiently screen novel thrombolytic therapies. We herein report the design, validation, and characterization of a highly reproducible, physiological scale, flowing clot lysis platform with real‐time fibrinolysis monitoring to screen thrombolytic drugs utilizing a fluorescein isothiocyanate (FITC)‐labeled clot analog. Using this Real‐Time Fluorometric Flowing Fibrinolysis assay (RT‐FluFF assay), a tPa‐dependent degree of thrombolysis was observed both via clot mass loss as well as fluorometrically monitored release of FITC‐labeled fibrin degradation products. Percent clot mass loss ranged from 33.6% to 85.9% with fluorescence release rates of 0.53 to 1.17 RFU/min in 40 and 1000 ng/mL tPa conditions, respectively. The platform is easily adapted to produce pulsatile flows. Hemodynamics of human main pulmonary artery were mimicked through matching dimensionless flow parameters calculated using clinical data. Increasing pressure amplitude range (4-40 mmHg) results in a 20% increase of fibrinolysis at 1000 ng/mL tPA. Increasing shear flow rate (205-913 s−1) significantly increases fibrinolysis and mechanical digestion. These findings suggest pulsatile level affects thrombolytic drug activities and the proposed in‐vitro clot model offers a versatile testing platform for thrombolytic drug screening.